2023
DOI: 10.7759/cureus.35162
|View full text |Cite
|
Sign up to set email alerts
|

Association of Asthma Control With Caregivers' Knowledge and Practices for Children With Asthma in the Tabuk Region of Saudi Arabia: A Cross-Sectional Study

Abstract: IntroductionAsthma is a chronic heterogeneous inflammatory disease that affects millions of individuals around the globe. Standardized asthma management is crucial to maintain and control the disease. Caregivers are the leading players in managing asthma during childhood. Studies are lacking in the Tabuk region. The aim of this study was to elucidate knowledge levels and common practices of caregivers of pediatric patients with asthma in the Tabuk region of Saudi Arabia and its impact on asthma control. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Similarly, Alsayed et al and Limaye et al showed that the extent of asthma control was significantly associated with caregivers' knowledge and practices for children with asthma [24,25].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Alsayed et al and Limaye et al showed that the extent of asthma control was significantly associated with caregivers' knowledge and practices for children with asthma [24,25].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the association between the maternal knowledge level and ER visits highlights the potential role of education in preventing asthma exacerbations and reducing healthcare utilization. Similarly, Alsayed et al and Limaye et al showed that the extent of asthma control was significantly associated with caregivers' knowledge and practices for children with asthma [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%